Perioperative gastrointestinal reflux in dogs. Issue 9 (1st November 2018) - Reid, Katherine
Abstract : Perioperative vomiting, regurgitation and reflux cause problems for veterinary patients during, but mostly after, anaesthesia. A history of gastrointestinal disease will often indicate the possibility of reflux, but many animals that regurgitate under anaesthesia have no previous history or predisposing factors, making this event an unwelcome surprise. If the refluxate fails to reach the larynx or mouth, the anaesthetist will be unaware and reflux will go untreated, with repeated incidents causing oesophagitis that can lead to stricture. Regurgitation complicates anaesthesia because animals have reduced or absent laryngeal reflexes and aspiration of refluxate leads to pneumonia. Following anaesthesia, irritation may make animals uncomfortable and less willing to eat, thus slowing their recovery and increasing any complications. This article aims to provide a greater depth of understanding as to why and how reflux occurs in anaesthetised dogs and what options are available for treatment.